A case of vascular leiomyosarkoma diminished with intravenous leiomyomatosis - Özlem Nuray Sever; Mehmet Sökücü (Journal of Oncological Sciences, 2019)
Leiomyosarcoma is a rare mesenchymal tumor of smooth muscle origin and up to 5% is caused by vascular smooth muscle. Vascular leiomyosarcoma is more common in women. The disease is often caused by large veins. Depending on the localization of the vein, different clinical pictures may be seen. As it is a rare tumor, there are difficulties in the clinical and pathological diagnosis of the disease. Standard recommendations on treatment are also not available.A 36-year-old female patient was admitted to our hospital with swelling in her left lower extremity. Physical examination of the patient was consistent with venous insufficiency findings. In the lower extremity venous doppler ultrasonography, there was grade 1 reflux in the left femoral vein. Medical treatment was performed. The patient was called for control after 1 month. The patient was re-admitted with deep vein thrombus. A repeat radiological examination revealed a mass in the left iliac vein. The patient was operated. The pathological diagnosis of the patient was evaluated in two centers. Finally, it was decided that the diagnosis was compatible with vascular leiomyosarcoma.Intravascular leiomyosarcoma can be overlooked in both clinical practice, radiological evaluation and histopathological examination because of its very rare occurrence. Keywords: Vascular leiomyosarcoma, Intravenous leiomyomatosis, Differential diagnosis